Sensory Neuropathy in Hypothyroidism: Electrophysiological and Clinical Findings - Yeasmin, Sabina; Begum, Noorzahan; Begum, Shelina; Rahman, Shah M Hafizur (Journal of Bangladesh Society of Physiologist, 2008)
Peripheral neuropathy may be a manifestation of hypothyroidism which usually develops insidiously over a long period of time due to irregular taking of drugs or lack of thyroid hormone replacement. The present study was designed to observe the clinical and electro-physiological findings in hypothyroid patients in order to evaluate the neuromuscular dysfunction as well as sensory neuropathy. For this purpose, 70 subjects with the age range of 20 to 50 years of both sexes were included in the study. Among them, 40 hypothyroid patients were taken in study group (Group B) and 30 aparently healthy subjects were taken as control (Group A). On the basis of their TSH levels, group B was further divided into group B1 with TSH <60 MIU /L or (less severe) and group B2 with TSH >60 MIU /L (severe group). The duration of the disease ranged from 6 months to 5 years. All the hypothyroid patients were selected from Thyroid Clinic, Center of Nuclear Medicine and Ultra sound, Dhaka Medical College and Hospital, Dhaka, during the period from January 2005 to December 2005. Healthy subjects were selected from personal contact. Most of the hypothyroid patients were under hormone replacement therapy. Diagnosis of hypothyroidism was done by serum levels of TT3, TT4 and the TSH. In this study, both TT3, TT4 levels were significantly (P<0.01) lower in hypothyroids in comparison to those of control. The patients were searched for the clinical signs of sensory neuropathy. Clinical findings revealed diminished or absence of most of the deep tendon reflexes. The nerve conduction studies for sensory nerve function were done in all the subjects by electrophysiological technique. All the tests were done in median and ulnar nerve for upper limb and in sural nerve for lower limb and these parameters were measured on the day 1 (one) of their first visit. Data were compared among the different groups. Most of the patients had higher sensory distal latencies (SDL) with lower conduction velocities (SNCV) which were more marked in severe cases. About 67.5% of hypothyroid patients had shown abnormal sensory NCV when compared to that of euthyroids. Therefore, this study concludes that sensory neuropathy may be a consequence of hypothyroidism. Key Words: Hypothyroidism; Neuropathy; Electrophysiology DOI:10.3329/jbsp.v2i0.975 J Bangladesh Soc Physiol. 2007 Dec;(2): 1-6.